Under pressure - Maric, Filip; Poto, Margherita Paola; Panieri, Giuliana; Peftieva, Olena (Septentrio Educational, 2023)
Focus: To understand and feel how water pressure changes with depth. Learning objectives: In this activity, pupils will recognize the relationship between water depth and pressure. Pupils will be able to reflect on how lifeforms in the deep sea might be affected by the high water pressures in their ecosystems. Key words: Depth, weight, pressure.